2011
DOI: 10.1007/s10549-011-1661-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the RNA effect of 26 DNA variants in the BRCA1 and BRCA2 genes

Abstract: Comprehensive genetic testing of the breast cancer susceptibility genes BRCA1 and BRCA2 identified approximately 16% of variants of unknown significance (VUS), a significant proportion of which could affect the correct splicing of the genes. Our aim is to establish a workflow for classifying VUS in these complex genes, the first stage of which is splicing analysis. We used a combined approach consisting of five in silico splicing prediction programs and RT-PCR analysis for a set of 26 variants not previously s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Normal mRNA splicing was observed for the remaining 5 variants of group B, including BRCA1 c.5333A>G and BRCA2 c.9116C>T, already analyzed [20][22] and BRCA1 c.548−3delT, c.594−4A>G, c.4097G>A, not previously characterized. To account for the possible occurrence of NMD, LCLs carrying these variants were analyzed following treatment with puromycin.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Normal mRNA splicing was observed for the remaining 5 variants of group B, including BRCA1 c.5333A>G and BRCA2 c.9116C>T, already analyzed [20][22] and BRCA1 c.548−3delT, c.594−4A>G, c.4097G>A, not previously characterized. To account for the possible occurrence of NMD, LCLs carrying these variants were analyzed following treatment with puromycin.…”
Section: Resultsmentioning
confidence: 66%
“…Numerous studies have shown that these tools may be used to predict whether BRCA1 and BRCA2 mutations located at splice sites and adjacent regions are expected to have an effect on mRNA splicing [13][18], [20][22], [24][27]. Therefore, they have been proposed to be instrumental in UV classification.…”
Section: Introductionmentioning
confidence: 99%
“…There are 4 instances of inconsistent or conflicting splicing results (6, 8, 14, 16-19). These include BRCA1 c.212+3A>G, c.670+8C>T, and c.736T>G and BRCA2 c.517-19C>T (4, 19-25).…”
mentioning
confidence: 99%
“…These include BRCA1 c.212+3A>G, c.670+8C>T, and c.736T>G and BRCA2 c.517-19C>T (4, 19-25). Reports of splicing results from a further 7 variants differed in the number of aberrant bands found in each study.…”
mentioning
confidence: 99%
“…Three BRCA2 recurrent mutations were identified (c.2808_2811delACAA, c.3264dupT and c.9026_9030delATCAT), representing 21.3 % of the total mutations (Table 4). These recurrent mutations have also been found in ICs and most of them have already been reported in studies carried out in Spanish population [26][27][28][29][34][35][36][37][38] or included in mutation databases [30,31] (Table 4). …”
Section: Discussionmentioning
confidence: 91%